TINJAUAN PERLINDUNGAN KONSUMEN ATAS KERUGIAN JASA PADA PENANAMAN MODAL MENURUT UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - IHCHAN PAUZI; PUGUH AJI HARI SETIAWAN; HARTANA HARTANA (SETARA : Jurnal Ilmu Hukum, 2023)
The rise of investment fraud in Indonesia, so there must be legal protection for consumers. The desire of consumers is to demand compensation for cases of fraud they have suffered. Therefore, the issues that arise is, What is the legal certainty regarding the Consumer Protection Act regarding the rights of victims to violations of investment services based on legal norms in Indonesia? To obtain essential information regarding these issues, the research approach used in this research is normative legal research. The data used includes tertiary legal materials, secondary legal materials, and primary legal materials. Primary data is also used to assist secondary data. Qualitative legal analysis method was used for data analysis. The research results obtained, there are several problems and law enforcement factors. Then based on the findings of the analysis, the judge determines the punishment for the perpetrators of crimes in the field of investment services in accordance with existing laws, legal certainty becomes the basis for compensation for victims of investment fraud.